If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + 10x = 4x + 15 Reorder the terms: -9 + 10x = 15 + 4x Solving -9 + 10x = 15 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -9 + 10x + -4x = 15 + 4x + -4x Combine like terms: 10x + -4x = 6x -9 + 6x = 15 + 4x + -4x Combine like terms: 4x + -4x = 0 -9 + 6x = 15 + 0 -9 + 6x = 15 Add '9' to each side of the equation. -9 + 9 + 6x = 15 + 9 Combine like terms: -9 + 9 = 0 0 + 6x = 15 + 9 6x = 15 + 9 Combine like terms: 15 + 9 = 24 6x = 24 Divide each side by '6'. x = 4 Simplifying x = 4
| 9=12x^2-23x | | -77.08=9.4y | | 2x-1-4=0 | | -0.56m=4.592 | | 2.3x=14.582 | | 2c+4=14 | | 5/6z-100 | | 13-6m=4-6m | | 3^4/5*3^3/x | | 11k=13t-7k/2t | | 6b^2+48b=0 | | -243=-9(10+n) | | 2x-4-(12+4x)=3x | | 3q^2-6q+2=0 | | 24+3y=24+2x | | x/10=1/4 | | 2x=x*2-15 | | 29x=5x+21+3x | | 4.3x+2=-1 | | A-b-5=p | | S^2-6s+4=0 | | (9m+11)(m+9)=79 | | -7x^2+15x+15=0 | | -8x^2+2x+10=0 | | 277.5-2.5t=555-16t^2 | | ry=x-45 | | 2[w-(2w+19)+14]=2(w+5) | | 10x-11+x^2=0 | | 7x-2(6-x)+2=18 | | (x-2)(x+5)=60 | | x^2-3x=-2x | | 8=m/4= |